Desenvolvimento de uma aplicação para monitoramento utilizando conceitos de internet das coisas - Noleto, Pedro Henrique Cavalcante (Universidade Federal do Tocantins, 2020)
Society is going through an irreversible technological process in the way of relating to the world. The technological revolution now underway is bringing to the fore technologies that will change the way we work, live and relate. In this context, the term “internet of things” (IoT) stands out among the many innovations emerging from the technological revolution. Machine learning, cloud storage, artificial intelligence and monitoring are some of the many possibilities that IoT offers, bringing with it new opportunities and participating effectively in the process of breaking with traditional business models. This work consists in the development and analysis of an application for monitoring the ambient temperature through the integration of several open source platforms and the use of IoT tools, allowing for cloud storage and databased actions, as well as the generation of graphs of the data obtained on computer and smartphone. Finally, considerations are made regarding the proposed infrastructure and its potential for application in the various areas of electrical engineering.